The Influence of Executive Character, Sales Growth, and Corporate Governance on Tax Avoidance (Empirical Study of Non-Cyclical Consumer Sector Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period) - Fitri, Prisca Aulia; Yulianto, Yulianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study aims to analyze the effect of executive character, sales growth, and corporate governance on tax avoidance. This research was conducted  by analyzing the financial statement of companies in the consumer non cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. The sample used in this study was 17 consumer non cyclical sector companies listed on the Indonesia Stock Exchange during the period from 2018 to 2022 using a puposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this study are Executive Character (X1) as the first independent variable, Sales Growth (X2) as the second independent variable, and Corporate Governance (X3) as the third independent variable and Tax Avoidance (Y) as the dependent variable. Panel data regression method is used as a research methodology in this study. Analysis of research results using the help of Eviews 12 software. The result showed that the best model is the Random Effect Model (REM). The results of this study indicate that Executive Character partially has a negative effect on Tax Avoidance, Sales Growth partially has no effect on Tax Avoidance, Corporate Governance partially has no effect on Tax Avoidance, and simultaneously Executive Character, Sales Growth and Corporate Governance effects on Tax Avoidance.